Clinical characteristics and predictive mortality risk factors in hospitalised children with COVID-19 illness during the first and second wave: single centre experiences from a tertiary paediatric hospital in Mumbai - Prabhu, Shakuntala S.; Gavali, Vrushabh S.; Mathur, Radhika; Rao, Sudha; Shobhawat, Lakshmi; Venkatesh, Sumitra; Prabhu, Sanjay; Bodhanwala, Minnie (International Journal of Contemporary Pediatrics, 2021)
Background: Coronavirus disease 2019 (COVID-19) pandemic has affected both adults and children alike. It presented in cluster of cases in short period of time all across the world. In India, there were two such clusters called as first and second wave. World over mortality was more in adults than in children. But, few children also had severe disease during these waves. Also, some presented with inflammatory state secondary to COVID-19 infection which is called as Multisystem Inflammatory syndrome in children (MIS-C). As major population affected with severe disease were older people this disease in initial phases was most studied in this population. It is thus necessary to observe and analyse disease manifestations, pattern and risk factors in children and also contrast these variables between the two waves. The objectives of the study was to compare and contrast clinico-demographic parameters and outcome predictors in children admitted with COVID-19 during the first and second waves. Methods: This is a retrospective analytical study comparing aforementioned parameters of children (with and without co-morbidity) admitted with COVID-19 infection between the two waves of pandemic in a tertiary care public pediatric hospital in Western Maharashtra. Results: First wave had 176 cases admitted over six months while the second wave had 185 cases over only three months. While proportion of cases with pneumonia requiring ICU stay was significantly higher in wave 2, those with MIS-C requiring inotropes was higher in wave 1. There was no difference in other clinico-demographic parameters of these cases irrespective of co-morbidity. Pneumonia, severe disease, hypoxia, need for inotropes or ICU care predicted poor outcome in both the waves. Conclusions: Though the pattern of presentation was different, the clinico-demographic variables and predictors of mortality were comparable between the two waves.